Versatile Utility of Cp*Co(III) Catalysts in C–H Amination under Inner- and Outer-Sphere Pathway - Lee, Jeonghyo; Chang, Sukbok (Synlett, 2023)
This Account describes the recent advances in our research program toward the development of cobalt-catalyzed C–H amidation reactions. In particular, synthetic versatilities of obtainable amino products shown to be achieved on the basis of two distinctive mechanistic scaffolds; inner- and outer-sphere pathways. It highlights our approaches to transit the modes of C–N bond formation by introduction of bidentate LX-type ligands into Cp*Co(III) precursors, thereby broadly expanding the scope of amination reactions.1 Introduction2 Cp*Co-Catalyzed Inner-Sphere C–H Amidation3 Cp*Co-Catalyzed Outer-Sphere C–H Amidation3.1 C(sp2)–N Bond Formation3.2 C(sp3)–N Bond Formation4 Conclusion
Keywords: cobalt catalysis; C–H amidation; chelation-assisted amidation; nitrenoid insertion; site-selective amidation